Immunological and virological triggers of type 1 diabetes: insights and implications - Lemos, Joana R. N.; Hirani, Khemraj; von Herrath, Matthias (Frontiers in Immunology, 2024)
Type 1 diabetes (T1D) is caused by an autoimmune process which culminates in the destruction of beta-cells in the pancreas. It is widely believed that a complex and multifactorial interplay between genetic and environmental factors, such as viruses, play a crucial role in the development of the disease. Research over the past decades has shown that there is not one single viral culprit, nor one single genetic pathway, causing the disease. Rather, viral infections, most notably enteroviruses, appear to accelerate the autoimmune process leading to T1D and are often seen as a precipitator of clinical diagnosis. In support of this hypothesis, the use of anti-viral drugs has recently shown efficacy in preserving beta-cell function after onset of diabetes. In this review, we will discuss the various pathways that viral infections utilize to accelerate the development of T1D.There are three key mechanisms linking viral infections to beta-cell death: One is modulated by the direct infection of islets by viruses, resulting in their impaired function, another occurs in a more indirect fashion, by modulating the immune system, and the third is caused by heightened stress on the beta-cell by interferon-mediated increase of insulin resistance. The first two aspects are surprisingly difficult to study, in the case of the former, because there are still many questions about how viruses might persist for longer time periods. In the latter, indirect/immune case, viruses might impact immunity as a hit-andrun scenario, meaning that many or all direct viral footprints quickly vanish, while changes imprinted upon the immune system and the anti-islet autoimmune response persist. Given the fact that viruses are often associated with the precipitation of clinical autoimmunity, there are concerns regarding the impact of the recent COVID-19 pandemic on the development of autoimmune disease. The long-term effects of COVID-19 infection on T1D will be discussed, including the increased development of new cases of T1D.Understanding the interplay between viral infections and autoimmunity is crucial for advancing our knowledge in this field and developing targeted therapeutic interventions. Here, we will examine the relationship between viral infections and autoimmunity and discuss potential considerations for prevention and treatment strategies.